IoT-Based Environmental Condition Monitoring System - Heng, Qiao Hui (Universiti Sains Malaysia, 2018)
Undesirable environmental factors have potential to bring low performance to certain companies or industries. Besides, it even brings hazards which may cause fatal injuries. With a reliable environmental monitoring system, it can warn the users immediately by providing sound alert if the environment is under unsafe status. On the other hand, different users may require different environmental parameters to be monitored. Therefore, a universal system should be considered to cater for a wide range of users. In the project, an environmental monitoring system called IoT-Based Environmental Monitoring System (IoTEMS) was built. IoTEMS is an embedded system that can be universally used to monitor 11 environmental parameters, which are temperature, humidity, light intensity, dust level, air pressure, liquified petroleum gas (LPG) concentration, carbon monoxide (CO) concentration, smoke concentration, flame level, sound intensity, and water level through a website. The system was programmed to obtain analogue data from the sensors and then the data will be stored to a database. For user interface (UI) purpose, a website-based system was developed that to allow the users to monitor the sensor data according the type of environmental parameters through the website. The website was designed that for each of the selected parameters, the value, the status, and the time of data acquisition can be observed. Several experiments were carried out to verify the functionality of all sensors. IoTEMS provides various environmental sensors that the system is not only restricted in one environment but can be applied in other environmental condition such as indoor area, outdoor area or even certain industries. IoTEMS can also enhance the effectiveness of the production in certain companies or industries by providing alarm hazardous conditions.